Therapeutic Potential of Heparin in Sepsis Per Gram Negative - Martínez, Javier Alfredo Pérez; Saavedra, Antonio José Gipis; Bohorquez, Guillermo David Barros; Cordero, Jhon Fredy Bello; Barros, Bryan Daniel; Ríos, María Kamila Muñoz; Duque, Leonardo Eduardo Dussan; Martínez, Leonardo José Mier (Jour Med Resh and Health Sci, 2022)
Background: Heparin is the oldest anticoagulant used in clinical medicine. Heparin has been studied for various applications and modifications. Gram-negative bacteria are among the most important public health problems in the world due to their high resistance to antibiotics. Methodology: A narrative review was carried out through various databases from January 2012 to December 2021; the search and selection of articles was carried out in journals indexed in English. The following were used as keywords: Heparin, sepsis, Gram negative. Results: Key factors in the development of sepsis include the release of pro-inflammatory mediators, diffuse endothelial injury, and procoagulant reactions, followed by organ dysfunction, taking into account that pro-inflammatory mediators activate coagulation. Heparin is a glycosaminoglycan with anticoagulant properties and anti-inflammatory effects. Conclusions: This review offers updated information on the therapeutic role of heparin in patients who develop sepsis after infection with Gram-negative bacteria.